Developing a mathematical model to predict energy expenditure while bouncing on a trampoline - Alexander, K.; Clement, T.; Draper, N. (European Journal of Sport Science, 2021)
Trampolining has become a popular recreational activity, but currently no method exists by which energy expenditure can be indirectly measured while bouncing. Therefore, the aim of this study was to produce a model to measure energy expenditure while bouncing on a trampoline. To achieve this, the study was completed in two stages. First, a model was developed which calculated the energy absorbed by the trampoline for a known weight. This was achieved using drop tests on a trampoline. Second, the efficiency of energy conversion while trampolining was measured. This involved healthy adults bouncing on a trampoline while energy expenditure was recorded using a gas analyser. The combined datasets from the two parts allowed the formation of a model which can predict energy expenditure while bouncing on a trampoline using only the user`s weight as an input. This model can now be used with an on-trampoline measurement method to track energy expenditure while jumping, thereby facilitating the use of trampolines for health and fitness.